(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
This article explores the phenomenon of synonymy in modern English, analyzing its nature, classification, causes, and significance in linguistic communication. Synonymy is an essential lexical phenomenon that enriches vocabulary, allows for stylistic variation, and facilitates precise expression in both written and spoken forms of the English language.